KENDALI SUHU PADA MESIN HOSTIA BAKING OVEN MENGGUNAKAN SENSOR THERMOCOUPLE TIPE K - Adhika Pradipta (Electro Luceat, 2022)
The development of the manufacturing world, especially in the field of industrial automation, is currently growing rapidly. Industrial automation is one of the efforts of industrial players, both large, medium and small scale industries to increase product productivity. One of the implementations of automation is in the manufacture of tools for making hosts. Making tools for the process of making hosts aims to facilitate the bread maker and maintain the quality of the bread. The parameter that determines the quality of the host created is the roasting process. The proper roasting process will produce a high quality host that requires the temperature to maintain this variable. This publication discusses the application of temperature sensors and temperature control to control the temperature on the Hostia Oven Bakery Machine. A Type K Thermocouple temperature sensor is used as input to the controller. The controller in this system uses the Temperature Controller TK4S-14RN . Testing the working system is done by comparing the temperature reading of the temperature controller with the ThermoGun. The time it takes the engine to reach working temperature when it is first turned on is 27 minutes. Error values ​​at temperature readings above 120oC with an average error value of 1.6oC-2.8 oC characteristics of the use of thermocouples such as reading at high temperatures affect the performance of temperature control on the hostia bakery machine.